Descriptive Study of Interpersonal Communication Patterns Between Parents and Children in Motivating Learning - Nursyamsia Nursyamsia; Siti Rahmi (ASHA Publishing, 2025)
This study aimed to describe the pattern of parent–child dyadic interpersonal communication in motivating children's learning in RT 05, Pantai Amal Baru Village. The study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews and documentation involving four parents and two children as research informants. The analysis was based on DeVito’s interpersonal communication theory, which includes five dimensions: openness, empathy, supportiveness, positiveness, and equality. The findings revealed that the quality of dyadic interpersonal communication varied among families. The first family demonstrated a higher level of openness, empathy, supportiveness, positive attitudes, and equality compared to the second family. Parents who actively communicated, listened to children's experiences, provided emotional support, and involved children in communication tended to foster stronger learning motivation. Conversely, limited interaction caused by occupational demands and economic factors reduced the intensity of communication and parental involvement in children's education. Nevertheless, children generally showed openness and willingness to communicate with their parents regarding their learning experiences. The study concludes that effective dyadic interpersonal communication characterized by openness, empathy, supportiveness, positive attitudes, and equality plays an important role in enhancing children's learning motivation. Therefore, strengthening the quality of communication between parents and children is essential to create a supportive family environment for children's educational development.